The increase of the stability of dental solid tissues to caries by iodine-containing thyroid hormones (LLC "Endo Press", 2020)
In experiments with 390 outbred male rats that were: 1) on the cariogenic diet of Stefan (for 2 months), 2) under crowding stress (40 individuals in the cage for the first month, 30 for the second month), 3) a combination of those factors, it has been established that hypothyroidism (injection of Mercazolil in the dose 25 mg/kg during the first month, then in a half dose till the end of the experiment) reduces, while small doses of L-thyroxine (1,5 - 3,0 mcg/ kg for 28 days, then - 1,5 mcg/kg until the end of the study), on the contrary, increase the resistance of dental solid tissues to caries. The dental solid tissues resistance increase to caries by iodine-containing thyroid hormones is caused by the increase of the structural and functional stability of the enamel, its density, the mineralizing potential, the level of calcium and the antioxidant activity in the saliva.